Open veins of Latin America five centuries of the pillage of a continent - Galeano, Eduardo 1940-2015; Cedric Belfrage; Isabel Allende (London Serpent's Tail, 1997)
Also includes sections on the slave trade, sugar in Cuba and the Caribbean.
Mankind's poverty as a consequence of the wealth of the land -- Lust for gold, lust for silver -- King sugar and other agricultural monarchs -- Invisible sources of power -- Development is a voyage with more shipwrecks than navigators -- Tales of premature death -- Contemporary structure of plunder -- Seven years after.
Translation of Las venas abiertas de Amâerica Latina.
Includes bibliographical references.
Keywords: Capitalism -- Latin America -- History; Latin America -- Economic conditions